Contrast-enhanced ultrasonography for differential diagnosis of adnexal masses - Shentu, Weihui; Zhang, Yin; Gu, Jiaojiao; Wang, Fa; Zhao, Wei; Liu, Chunmei; Lin, Zimei; Wang, Yao; Liu, Chen; Chen, Yunyu; Fan, Qiyun; Wang, Hongying (Frontiers in Oncology, 2022)
Background: Quantitative contrast-enhanced ultrasonography parameters are affected by various factors. We evaluated corrected quantitative contrast enhanced ultrasonography in differentiating benign adnexal tumors from malignant tumors. Methods: Patients with adnexal masses who underwent conventional and contrast-enhanced ultrasonography were included. Contrast-enhanced ultrasonography parameters such as base intensity, arrival time, peak intensity, time to peak intensity, ascending slope, and descending slope were measured. Corrected (time to peak intensity − arrival time) mass / (time to peak intensity − arrival time) uterus and (peak intensity − base intensity) mass / (peak intensity − base intensity) uterus were calculated. Lesions were confirmed by pathologic examination of surgical specimens. Results: This study included 31 patients with 35 adnexal lesions including 20 (57.10%) benign and 15 (42.90%) malignant lesions. The corrected contrast-enhanced ultrasonography quantitative parameters in lesions were statistically different between malignant and benign groups (P<0.05). The optimal cut-off value for (time to peak intensity − arrival time) mass / ( time to peak intensity − arrival time) uterus, ascending slope, and (peak intensity − base intensity) mass/( peak intensity − base intensity) uterus, and descending slope for differentiating malignant adnexal masses from benign tumors were 1.05 (area under curve: 0.93, P<0.05), 1.11 (area under curve: 0.83, P<0.05), 0.82 (area under curve: 0.73, P<0.05), and −0.27 (area under curve: 0.66, P=0.16), with sensitivity and specificity of 93.33% and 85.00%, 86.67% and 75.00%, 86.67% and 60.00%, and 54.55% and 66.67%, respectively. Conclusions: Corrected contrast-enhanced ultrasonography parameters provide practical differential diagnosis value of adnexal lesions with high reliability for radiologists.